Statistical shape model-based planning organ-at-risk volume: application to pancreatic cancer patients. (13th January 2021) - Nakamura, Mitsuhiro; Nakao, Megumi; Mukumoto, Nobutaka; Ashida, Ryo; Hirashima, Hideaki; Yoshimura, Michio; Mizowaki, Takashi
Abstract: Purpose . To introduce the concept of statistical shape model (SSM)-based planning organ-at-risk volume (sPRV) for pancreatic cancer patients. Methods . A total of 120 pancreatic cancer patients were enrolled in this study. After correcting inter-patient variations in the centroid position of the planning target volume (PTV), four different SSMs were constructed by registering a deformable template model to an individual model for the stomach and duodenum. The sPRV, which focused on the following different components of the inter-patient variations, was then created: Scenario A: shape, rotational angle, volume, and centroid position; Scenario B: shape, rotational angle, and volume; Scenario C: shape and rotational angle; and Scenario D: shape. The conventional PRV (cPRV) was created by adding an isotropic margin R (3–15 mm) to the mean shape model. The corresponding sPRV was created from the SSM until the volume difference between the cPRV and sPRV was less than 1%. Thereafter, we computed the overlapping volume between the PTV and cPRV (OLc ) or sPRV (OLs ) in each patient. OLs being larger than OLc implies that the local shape variations in the corresponding OAR close to the PTV were large. Therefore, OLs /OLc was calculated in each patient for each R- value, and the median value of OLs /OLc was regarded as a surrogate for plan quality for each R- value. Results . For R  = 3 and 5 mm, OLs /OLc exceeded 1 for the stomach and duodenum in all scenarios, with a maximum OLs /OLc of 1.21. This indicates that smaller isotropic margins did not sufficiently account for the local shape changes close to the PTV. Conclusions . Our results indicated that, in contrast to conventional PRV, SSM-based PRVs, which account for local shape changes, would result in better dose sparing for the stomach and duodenum in pancreatic cancer patients.